Equilibrium Kinetic Analysis of a Model Mixture of Anthracene and Benzothiophene - Baikenov, M.I.; Tateeva, A.B.; Akhmetkarimova, Zh.S.; Tusipkhan, A.; Mataeva, A.Zh.; Esenbaeva, K.K. (Allerton Press, 2015)
The kinetic and thermodynamic parameters of the hydrogenation of an anthracene–ben􀀀 zothiophene model mixture were calculated. The rate constants of forward and reverse reactions, the equilib􀀀 rium constant, the activation energies, and the heat effects of hydrogenation reactions were determined by equi􀀀 librium kinetic analysis for second􀀀order reactions in a model mixture of anthracene and benzothiophene in the presence of an iron􀀀containing catalyst over a temperature range of 648–698 K at a pressure of 6 MPa.